A Dibenz[a, h]Anthracene-Degrading Strain Amycolatopsis sp. Y1-2 from Soils in the Coal Mining Areas. (1st January 2020) - Xu, Hong-Ying; Ge, Jing-Li; Zhang, Ling-Li; Zhang, Chan; Jin, Ru; Wang, Xiao-Hui
Abstract: It is well-known that the high-molecular-weight polycyclic aromatic hydrocarbons (HMW-PAHs) are difficult to degrade, and they can cause tremendous damaging effects in environment. In this article, a novel dibenz[a, h]anthracene (DBA)-degrading strain Amycolatopsis sp. Y1-2 was isolated and identified from the contaminated soils in the coal mining areas. The degradation of HMW-PAHs by strain Y1-2 could be improved by adopting DBA, benzo(a)anthracene, benzo(b)fluoranthene, benzo(a)pyrene, and benzo(g, hi)perylene as the sole carbon and energy sources. The co-metabolism substrates test revealed that the HMW-PAHs degradation efficiency of strain Y1-2 could be significantly improved under co-metabolism substrates, especially glucose (increased by 34.70%) and cyclodextrin. The optimization results of DBA-degrading conditions obtained from response surface analysis are as follows: pH 7.6, concentration of DBA 10.71 mg L −1, inoculum amount 1.58 g 100 mL −1 medium, concentration of glucose 9.98 g L −1, and concentration of cyclodextrin 2.05 g L −1 . The predicted value of degradation percentage in the optimized conditions was 99.03% (very similar with the actual value of 97.84%). Based on the above results, the strain Y1-2 can degrade HMW-PAHs effectively and will be applied in treating PAHs-containing soils and industrial wastewater.